PENGEMBANGAN CANDI SAMBISARI SEBAGAI WISATA PURBAKALA DAN BUDAYA - , DEWI SULISTYANINGRUM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sambisari Temple is one of temple that is located in Sleman regency, Yogyakarta. This research discusses about development of Sambisari Temple as archeological and culture tourism destination. In this research will be analysis with use SWOT and market segmentation (tourist) from 3 components of tourism product, that is attraction component, amenity and accessibility. The result from the research is strategy with the programs planning which could did in Sambisari Temple as archeological and culture tourism destination. The research was conducted by collecting data by direct observation to location, questionnaires, interview with visitors and relevant parties templeâs management, as well as data in the form of documentation. Key word: Sambisari Temple, cultural tourism, 3A component